Impact of weight variability on mortality among Korean men and women: a population based study - Daein Choi (Nature Portfolio, 2019)
Abstract The health consequences of weight fluctuation have been controversial and little-studied within Asian populations. We aimed to determine the effect of weight variability on mortality using Korean National Health Insurance Service – National Health Screening Cohort. Weight variability was defined as the average successive variability of body mass index (BMI) of the first (2002 and 2003), second (2004 and 2005), and third (2006 and 2007) health examinations. Then, we used Cox regression models to estimate the effect of weight variability on mortality. Compared to participants within the first quintile (lowest) of weight variability, those within the fifth quintile (highest) had increased the risk of death from all causes (hazard ratio, HR 1.33, 95% confidence interval, CI 1.26–1.41), cardiovascular disease (HR 1.31, 95% CI 1.12–1.53), cancer (HR 1.11, 95% CI 1.02–1.22), and other causes (HR 1.58, 95% CI 1.45–1.73). The risk-increasing effect of weight variability on mortality was preserved after excluding past and current smokers as well as those with pre-existing cardiovascular disease or cancer. In conclusion, high weight variability may lead to elevated risk of death even among healthy never smokers. Therefore, maintaining a steady weight should be recommended to benefit from reduced risk of death.